Photodissociation of atmospherically important species - Tyley, P (2000)
﻿ The photodissociation of ozone by ultraviolet light has a great impact on the photochemistry of the atmosphere. The relative quantum yield for the production of the singlet atomic fragment O(1D) has been determined in the wavelength region 306 to 327 nm for four temperatures between 227 K and 300 K. The technique of resonance enhanced multi photon ionisation (REMPI) was used to probe directly the O(1D) photolysis product. These relative measurements have been placed onto an absolute scale by the selection of a calibration point whose value has been agreed by the scientific community. The yields obtained are in good agreement with others reported during the time of the research reported in this thesis and clearly show that three mechanisms contribute to the final quantum yield. Below 310 nm, O(1D) is produced by a spin-allowed channel, above 320 nm the primary channel is a spin- forbidden one and at intermediate wavelengths photolysis of vibrationally excited ozone contributes to the O(1D) yield. Elements of the quantum yield data presented in this thesis are being included in a new recommendation for the temperature dependent O(1D) quantum yield. Details of the dissociation kinetics, including further evidence confirming the spin-forbidden channel, is presented in time-of-flight studies of the O(1D) product. Time-of-flight profiles taken between 317 and 321 nm show evidence that, at room temperature, the O(1D) quantum yield is anti-correlated with the ozone absorption cross section. Excitation of the O2(a1Δg) co-fragment has been observed at wavelengths below 296 nm by monitoring the energies of the O(1D) formed. As the channel for the production of O2(a1Δg,andnbsp;vandnbsp;=andnbsp;1) opens, it is found that energy is preferentially partitioned into rotation of the O2 fragment rather than into translation. Initial studies on the O(1D) fragment have shown that the fragment is orbitally aligned and that the choice of REMPI transition can have a significant effect on the time-of-flight profiles and therefore on the measurements that are made from the profiles. The time-of-flight profiles obtained by probing the O2(a1Δg) photofragment have shown that the O2(a1Δg) has an angular momentum polarisation that is J dependent, with the even J being strongly polarised and the odd J depolarised. This results in the shape of the time-of-flight profiles being a function of the REMPI laser polarisation; and the study of this behaviour has been used to confirm the assignments in highly perturbed REMPI spectra.